2014
DOI: 10.1148/radiol.13122834
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Bilayer Barium Sulfate–Bismuth Oxide Composite Thyroid Collars for Superior Radiation Protection in Fluoroscopy-guided Interventions: A Prospective Randomized Controlled Trial

Abstract: Purpose:To test whether newer bilayer barium sulfate-bismuth oxide composite (XPF) thyroid collars (TCs) provide superior radiation protection and comfort during fluoroscopy-guided inter ventions compared with standard 0.5-mm lead-equivalent TCs. Materials and Methods:Institutional review board approval and written informed consent were obtained for this HIPAA-compliant study, and 144 fluoroscopy-guided vascular interventions were included at one center between October 2011 and July 2012, with up to two operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…[ 50 ] The Ba@Bi‐GLUE is made from heavy metal materials, for example, Ba and Bi, which can sharply attenuate radiation and have been widely used in radiation shielding. [ 51 ] We envision that when the GI tract is coated with Ba@Bi‐GLUE as an intracorporal radiation shield, [ 52 ] it may protect the neighboring GI tract and other healthy tissue from the high radiation exposure (Figure 8a; Figure S31, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 50 ] The Ba@Bi‐GLUE is made from heavy metal materials, for example, Ba and Bi, which can sharply attenuate radiation and have been widely used in radiation shielding. [ 51 ] We envision that when the GI tract is coated with Ba@Bi‐GLUE as an intracorporal radiation shield, [ 52 ] it may protect the neighboring GI tract and other healthy tissue from the high radiation exposure (Figure 8a; Figure S31, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a large area of GI-tract imaging, Bi-GLUE can also be used to construct an intracorporal radiation shield by covering the GI tract with a uniform layer of radiation-attenuating material. [51,52] In the whole-abdomen irradiation model of rats, Ba@Bi-GLUE protected the GI tract from radiation damage, leading to greatly decreased GI radiotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…PRPE layers can consist of a single attenuating layer, while others consist of a bilayer structure, the latter designed to account for fluorescent X-rays [ 21 , 27 , 28 ]. The brands mentioned in Table 2 are all composed of lead-free materials except Brand C (lead-composite).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated the effect of barium sulfate composite thyroid collars and apron on radiation protection for operators during the use of fluoroscopy and X-ray [ 15 , 16 ]. However, there has been no study investigating the effect of patient organ shield during C-arm fluoroscopic examination.…”
Section: Discussionmentioning
confidence: 99%